1991
DOI: 10.1093/carcin/12.5.839
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effect of malachite green on the development of hepatic pre-neoplastic lesions induced by N-nitrosodiethylamine in rats

Abstract: The effects of malachite green (MG) and phenobarbitone (PB) were compared on the development of pre-neoplastic lesions during N-nitrosodiethylamine(DEN)-induced hepatocarcinogenesis in male Wistar rats. Rats were administered 200 p.p.m. DEN in drinking water for a period of 1 month. After an interval of 2 weeks the animals were given either MG (25 p.p.m.) or PB (500 p.p.m.) in drinking water for 2.5 months. The effects were monitored on the basis of the morphological appearance of the liver, histological patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 0 publications
0
60
0
Order By: Relevance
“…But a recent report by Culp et al (1999) showed a dose-dependent increase of DNA adducts in the liver of mice and rats after 28 days of feeding MG in concentrations up to 600 ppm. MG promoted pre-neoplastic lesions of the liver after induction with N-nitrosodiethylamine (Fernandes et al, 1991;Gupta et al, 2003).…”
Section: Figure 1: Flow Chart Depicting Data Sources and Individual Smentioning
confidence: 97%
“…But a recent report by Culp et al (1999) showed a dose-dependent increase of DNA adducts in the liver of mice and rats after 28 days of feeding MG in concentrations up to 600 ppm. MG promoted pre-neoplastic lesions of the liver after induction with N-nitrosodiethylamine (Fernandes et al, 1991;Gupta et al, 2003).…”
Section: Figure 1: Flow Chart Depicting Data Sources and Individual Smentioning
confidence: 97%
“…It is used as a food colouring agent, food additive, a medical disinfectant, antihelminthic product and also as dye in silk, wool, jute, leather, cotton, paper and acrylic industries (Culp and Beland, 1996). However, due to the risks it poses to the consumers of treated fish, including its effects on the immune system, reproductive system and its genotoxic and carcinogenic properties (Fernandes et al, 1991;Rao, 1995;Gouranchat, 2000), malachite green has now become a highly controversial compound (Alderman and Clifton-Hadley, 1993). Malachite green is reported to cause carcinogenesis, mutagenesis, chromosomal abnormalities and physiological changes in animals (Omoregie et al, 1998;Srivastava et al, 2004).…”
mentioning
confidence: 99%
“…Although malachite green is not approved by the U.S. Food and Drug Administration, its worldwide use in aquaculture will probably continue due to its relatively low cost, ready availability, and efficacy (26); therefore, potential human exposure to malachite green could result from the consumption of treated fish (2) and from working in the dye and aquaculture industries. Malachite green is highly toxic to mammalian cells; it promotes hepatic tumor formation in rodents and also causes reproductive abnormalities in rabbits and fish (13,24). The structural similarity of malachite green to other carcinogenic triphenylmethane dyes also raises suspicion of carcinogenicity; gentian violet (crystal violet) is a thyroid and liver carcinogen in rodents (17), and pararosaniline is a bladder carcinogen in humans (7).…”
mentioning
confidence: 99%